Critical Thinking and Analytical Exposition Text in EFL Contexts: A Correlational Study - Rizka Nurul Atika; Suci Yulia Puspita; Tasya Arini (Instructional Development Journal, 2026)
This study investigates the correlation between students’ critical thinking and their ability in writing analytical exposition texts. The research was conducted using a quantitative correlational design involving 55 eleventh-grade students at a state Islamic senior high school in Pekanbaru. Data were collected through a critical thinking disposition questionnaire and a writing test. The findings indicate that students generally demonstrate moderate levels of critical thinking and writing ability. Statistical analysis using Pearson Product-Moment correlation reveals a significant positive correlation between the two variables. This suggests that students with higher critical thinking tend to produce better analytical exposition writing. The study highlights the importance of integrating critical thinking instruction into writing pedagogy to improve students’ academic writing performance.